2008
DOI: 10.1007/s15010-008-8165-1
|View full text |Cite
|
Sign up to set email alerts
|

Clustering and Risk Factors of Methicillin-Resistant Staphylococcus aureus Carriage in Two Italian Long-Term Care Facilities

Abstract: The study suggests that nursing homes are a significant reservoir for MRSA. Statistical and PFGE analyses indicate a scenario where MRSA seems to be endemic and individual risk factors, namely recent hospitalizations and repeated antibiotic treatments, play a major role in the selection of drug-resistant organisms. Infection control measures should be coordinated among different health care settings, and the appropriate use of antibiotics has emerged as an important issue for improving the quality of care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
1
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 35 publications
1
28
1
1
Order By: Relevance
“…Moreover, the other 18% of the patients received antibiotic prophylaxis and it was in 93% of the cases typically unnecessary prophylaxis for UTI. The wide use of antimicrobials is known to be a risk factor for multiresistant bacteria, especially in LTCFs [36,37]. The overuse of antibiotics clearly indicated that more guidance in the use of antimicrobials for infection or prophylaxis was needed and gave written feedback of the inappropriate use of antibiotics in the primary care wards.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the other 18% of the patients received antibiotic prophylaxis and it was in 93% of the cases typically unnecessary prophylaxis for UTI. The wide use of antimicrobials is known to be a risk factor for multiresistant bacteria, especially in LTCFs [36,37]. The overuse of antibiotics clearly indicated that more guidance in the use of antimicrobials for infection or prophylaxis was needed and gave written feedback of the inappropriate use of antibiotics in the primary care wards.…”
Section: Discussionmentioning
confidence: 99%
“…Nursing homes, with their growing elderly residents, are ideal for its growth. [2526] Places with overcrowding, such as prisons and dormitories, can facilitate the spread of MRSA. [27] Farm workers, especially those working with pigs, have apparently higher MRSA exposure.…”
Section: Predisposing Factorsmentioning
confidence: 99%
“…MDRO are regarded as a potentially serious threat to elderly people living in long-term care facilities (LTCFs). Although various studies on the prevalence of MRSA in LTCFs in Germany [7][8][9][10][11][12][13] and other European countries [14][15][16][17][18][19][20][21][22][23][24][25] have been published (< 1% in the Netherlands and Sweden, > 20% in Ireland and the United Kingdom (UK)), studies on the prevalence of MRGN such as extended-spectrum betalactamase (ESBL)-producing Enterobacteriaceae and vancomycin-resistant enterococci (VRE) among nursing home residents in German and in European LTCFs are scarce [7,14,24,26,27]. Although an increasing trend in the occurrence of ESBL-producing Enterobacteriaceae and even CRO is found in hospitals all over Europe [1,3,28,29], a lack of knowledge on multidrug-resistant organisms (MDRO) in nursing homes has to be stated.…”
Section: Introductionmentioning
confidence: 99%